Strategies for Managing Conflicts on Construction Sites in Abuja-Nigeria - Jimoh, Richard; Oyewobi, Luqman; Osajarikre, Jennivieve; Adaji, Adejoh; Sani, Momoh (Journal of Techno-Social, 2019)
Construction universally demand the contributions of several individuals, with each person bringing forward its specialist knowledge required to successfully bring the project to completion, have different interest but a common objective of project execution. However, when people of varying background come together, conflict is certainly not absent, as the members within the project interrelate interest collides and conflicts result, which can have adverse effects on the project delivery, especially when it is not well managed. Therefore, this paper assessed the strategies for managing conflicts on active construction sites in Abuja through the self-administration of structured questionnaires. Findings revealed that inadequate communication among project teams with a mean score of 3.52 which could be deemed as high extent among the causes of conflict on construction sites. In a related development, strategies such as jointly work with others to come up with consensual approach to with mean score of 4.34 is often used by the respondents in collaborating strategy. The paper concluded that the least favoured strategy adopted by the respondents was competing mode/style as compared to collaborating mode/style, compromising mode/style, avoiding mode/style, accommodating mode/style. The paper recommended that a system be put in place to facilitate and to enhance a smooth transmittance of information from one individual to another within the project team like team meeting discussions, site review meetings, and project status reporting.